Copula : sexual technologies, reproductive powers - Ferrell, Robyn, 1960- (SUNY series in gender theory., 2006)
"How will the ability to manipulate human reproduction change our social world and the relationship between the sexes? Taking an explicitly interdisciplinary approach to gender and reproductive technology, Robyn Ferrell examines this question in the light of feminist theories of sexual equality and sexual difference, arguing that technology itself can be seen as a kind of reproduction. Invoking a concept of reproduction that understands it as generic, Ferrell asserts that in any reproduction, something is produced of a kind that was there before and yet that is also new. Technology is therefore generically reproductive, since it produces new matter of the same kind. In addition to key figures in French feminism, Ferrell draws from psychoanalysis and contemporary continental thinkers ranging from Heidegger to Haraway."--Jacket.